Action Modulates the Conscious Reasoning Process of Moral Judgment: Evidence From Behavior and Neurophysiology - Leng, Yue; Zhang, Jili; Zhangyu, Yanan; Yang, Xiaoyuan (Frontiers in Behavioral Neuroscience, 2021)
Moral judgment can be highly affected by the action and intention factors at behavior level. Previous neuroimaging studies have demonstrated that the intention factor can modulate both the affective and cognitive processing of moral judgment. The present event-related potentials (ERP) study examined how the action factor modulated the neural dynamics of moral judgment under a newly developed moral dilemma paradigm including three different conditions: harm caused by action (i.e., doing harm), harm caused by omission (i.e., allowing harm), and no harm. Behavior data showed that participants preferred utilitarian judgments and spent less time for allowing harm condition than for doing harm condition. ERP results revealed that, compared with the doing harm and no harm dilemmas, the allowing harm dilemmas elicited enhanced N450 response associated with cognitive control and/or cognitive effort processes, but attenuated late positive potentials (LPP) response associated with top-down control of attention and cognitive ‘rational’ control processes. Such LPP amplitude differences were positively correlated with C-score of moral competence test which indexed the cognitive aspect of moral judgment competence. These findings suggested that people have strong omission bias, and such action factor modulates the conscious reasoning process during moral judgment, including the cognitive control and/or cognitive effort, and attentional allocation processes.